Effect of the conditioning and ultrasound-microwave sequential technique on the yield, chemical and functional properties of the essential oils and hydrolats extracted from the leaves of Tagetes elliptica Smith - Torre Alvarez, Ruben (2022)
Thermal regulation and ultrasound affect the physical, chemical, and antioxidant properties of essential oils and hydrosols extracted by microwaves from the leaves of Tagetes elliptica S. (chincho). The leaves were conditioned by dehydration or freezing, then pre-treated with ultrasound for 15 or 30 minutes at 40 Hz to finally obtain the essential oil (AECH) and hydrolat (HCH) through microwave extraction (500 W and 30 minutes). Yields, phenolic content, antioxidant capacity, leaf structure by optical microscopy, and chemical composition by gas chromatography and mass spectrometry (GC-MS) were evaluated. The conditioning of the leaves by freezing and sonication for 30 minutes obtained the best performance, 8.86±0.1% and 67.40 ± 4.8%, phenolic content of 39.4±0.1 mg EAG/mL and 346.2 ± 13.6 mg EAG/mL, and antioxidant capacity of 35.7 μmol EqT/mg and 0.25 μmol EqT/mg equivalent, for AECH and HCH, respectively in every case. Structural damage of the leaves was observed due to the effect of the conditioning-ultrasound-microwave treatments, achieving a more significant release of bioactive compounds. The main compounds of the essential oil were tagetenones (49.2%), followed by cis-miroxide (14.5%), dihydrotagetone (13.9%), tagetone (9.8%) and ocimene (2.4%); the main compounds in the hydrolate were cis-myroxide (44.66%), followed by cis- tagetone (23.84%), trans-tagetone (12.24%), linalool oxide (5.48%) and dihydrotagetone (4.04%). The significant contribution of the present study is the extraction techniques and chemical profile of tagetes elliptica extracts.